2019
DOI: 10.1016/j.jviscsurg.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of obstructive left colon cancer at a national level: Results of a multicentre study of the French Surgical Association in 1500 patients

Abstract: Surgical management of obstructive left colon cancer (OLCC) is controversial. The objective is to report on postoperative and oncological outcomes of the different surgical options in patients operated on for OLCC. Methods:From 2000-2015, 1500 patients were treated for OLCC in centers members of the French Surgical Association. Colonic stent (n=271), supportive care (n=5), palliative derivation (n=4) were excluded. Among 1220 remaining patients, 456 had primary diverting colostomy (PDC), 329 a segmental colect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
1
27
1
2
Order By: Relevance
“…Most studies on obstructive CRC report on the comparison with nonobstructive CRC and the efficacy of SEMS as BTS; there are few analyses on the prognostic factors of obstructive CRC. For BTS, there is no difference between decompression using a temporary stoma and SEMS [ 24 ]; many recent reports and meta-analyses show no difference in long-term outcomes between BTS using SEMS and emergency surgery [ 10 , 12 , 25 ]. Regarding BTS using TADT, small retrospective studies mostly from Japan showed no difference in outcomes from BTS using SEMS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on obstructive CRC report on the comparison with nonobstructive CRC and the efficacy of SEMS as BTS; there are few analyses on the prognostic factors of obstructive CRC. For BTS, there is no difference between decompression using a temporary stoma and SEMS [ 24 ]; many recent reports and meta-analyses show no difference in long-term outcomes between BTS using SEMS and emergency surgery [ 10 , 12 , 25 ]. Regarding BTS using TADT, small retrospective studies mostly from Japan showed no difference in outcomes from BTS using SEMS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Biondo et al reported that the presence of preoperative renal failure was a significant risk factor for mortality after obstructing colon cancer operations (p = 0.0005) (30). Contrarily, Mege et al also denied any significant impact of renal comorbidity on mortality after surgery for the same pathology (p = 0.33) (31).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Most of the studies on obstructive CRC report on the comparison with non-obstructive CRC and the e cacy of SEMS as BTS; there are few analyses on the prognostic factors of obstructive CRC. For BTS, there is no difference between decompression using temporary stoma and SEMS [24]; many recent reports and meta-analyses show no difference in long-term outcomes between BTS using SEMS and emergency surgery [10,12,25]. Regarding BTS using TADT, retrospective studies, which are small in size and mostly from Japan, show no difference from BTS using SEMS [26].…”
Section: Discussionmentioning
confidence: 99%